EXPERIMENT ON CHEMICAL ATTACHMENT OF ANCHOR DEFORM DEPTH 110 MM CAST-IN PLACE AND POST-INSTALLED DRILL BIT EXTRACTOR METHOD - Bastian Dwi Ananta; Henry Apriyatno (DAS Institute, 2022)
The anchor is one of the steel elements that can withstand the adhesive force against the concrete. The study aims to determine the adhesive strength between the anchor and the concrete through two anchor installation methods: the cast-in-place method with three test objects and post-installed chemical epoxy in two plain hole models with three test objects. And threaded three test specimens using a drill bit extractor Sika Anchorfix-2 chemical epoxy adhesive. Anchor deform model D13 is used with a depth of planting (hef) of 110 mm, which is planted on nine cylinders of 300 x 150 mm with a quality of fc 32.26 MPa. This study aims to determine the pulling capacity, adhesive strength, and damage patterns in the cast-in-place and post-installed methods. The results of the pull-in strength test using the cast-in-place method are 34323.28 N, the post-installed method is plain hole 37919.05 N, and the drill hole is 38572.82 N. The adhesive strength (µ) post-installed drill hole is 9.27 MPa > adhesive strength (µ) cast in place 7.64 MPa with an increase (phi) of 1.21 times, adhesive strength (µ) post installed plain hole 7.84 MPa > adhesive strength (µ) cast in place 7.64 MPa with an increase (phi) of 1 .03 times, adhesive strength (µ) post installed drill hole 9.27 MPa > adhesive strength (µ) post installed plain hole 7.84 MPa with an increase (phi) of 1.18 times. With a pullout failure pattern on all cylindrical test specimens.